The effect of cation–anion interactions on soil pH and solubility of organic carbon. (28th September 2015) - Tavakkoli, E.; Rengasamy, P.; Smith, E.; McDonald, G. K.
Summary: Alkaline soil is widely distributed and cultivated throughout the agricultural regions of the world. Organic carbon (OC) concentrations in alkaline soil are often small, partly because of the limitations of a high pH on the productivity of crops and pastures together with the effects of high pH on the chemistry of soil OC. Soil pH is often hypothesized to be a major factor in regulating OC turnover in agricultural soil, but there are few detailed studies on the effects of high pH on carbon cycling in alkaline soil. Sodium, K +, Mg 2+ and Ca 2+ are the major cations in alkaline soil, whereas Cl −, SO 4 2 −, H C O 3 − and C O 3 2 − are the major anions. The effect of different combinations of these cations and anions on soil pH and OC is not well described in the literature. The objectives of this study were to evaluate the effect of cations and anions on soil pH and to quantify the dissolution of OC in relation to these changes in pH. The results showed that H C O 3 − (Na +, K + and Mg 2+ ) salts and CaCO3 dominate in the pH range 7.0–8.5, and C O 3 2 − salts of Na + and K + dominate above pH 8.5. The amount of dissolved OC (DOC) increased significantly as pH increased. Therefore, the presence of large concentrations of H C O 3 − and C O 3 2 − not only increased pH but also promoted the dissolution of soil OC. The concentration of Ca 2+ modified this effect; large concentrations of Ca 2+ increased the adsorption and reduced the concentration of DOC.